2015
DOI: 10.1371/journal.pone.0127202
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Increased Survival after Surgical Resection of Glioblastoma in Octogenarians

Abstract: Elderly patients with glioblastoma represent a clinical challenge for neurosurgeons and oncologists. The data available on outcomes of patients greater than 80 undergoing resection is limited. In this study, factors linked to increased survival in patients over the age of 80 were analyzed. A retrospective chart review of all patients over the age of 80 with a new diagnosis of glioblastoma and who underwent surgical resection with intent for maximal resection were examined. Patients who had only stereotactic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…5 It remains debatable whether or not the preoperative volume of contrast enhancement is a prognostic factor for survival, as extent of resection is usually seen as a better measure of outcome. 1,3,11,23,24,28,31 In our study we found a limited, yet significant, effect of volume of contrast enhancement on survival. However, the volume of contrast enhancement could not explain the difference between the patient groups, and ventricle contact was identified as a strong independent prognostic factor.…”
Section: Discussioncontrasting
confidence: 47%
“…5 It remains debatable whether or not the preoperative volume of contrast enhancement is a prognostic factor for survival, as extent of resection is usually seen as a better measure of outcome. 1,3,11,23,24,28,31 In our study we found a limited, yet significant, effect of volume of contrast enhancement on survival. However, the volume of contrast enhancement could not explain the difference between the patient groups, and ventricle contact was identified as a strong independent prognostic factor.…”
Section: Discussioncontrasting
confidence: 47%
“…It is therefore worth mentioning the immunohistochemical outcomes that were observed in 33 patients. Consistent with previous studies, 28,29 in our study, we found a statistically significant relationship between low p53 expression in protein immunostaining and longer survival times. It has been suggested that an increase in the expression of p53 is a response to DNA damage.…”
Section: Original Articlesupporting
confidence: 93%
“…[27][28][29][30][31] Abdullah Kalil et al conducted a study on factors associated with increased survival after surgical resection on GBM patients of more than 80 years of age in which they found a statistically significant correlation between the KPS and overall survival. 30 In another study, Chaichana et al considered preoperative factors associated with decreased survival for older patients who underwent resection of a GBM, and found that one of the preoperative factors that was independently associated with decreased survival was a KPS score of less than 80. 31 Chaichana et al, in another study, evaluated functional outcomes over time for patients with glioblastoma, and found that a preoperative KPS score of !…”
Section: Discussionmentioning
confidence: 99%